A model for the multipath delay profile of fixed wireless channels. - Erceg, V. (IEEE Journal on selected areas in communications)
This paper deals with the measurement and modeling of multipath delay on fixed wireless paths at 1.9 GHz in suburban environments. The primary focus is on the delay profile, which is the normalized plot of received power versus delay in response to an RT ?impulse.? We describe measurement campaigns in the western suburbs of Chicago, IL, and in suburban north-central New Jersey. Our analysis of the data suggests to us that, for directive terminal antennas, the delay profile can be modeled as having a ?spike-plus-exponential? shape, i.e., a strong return (?spike?) at the lowest delay, plus a set of returns whose mean powers decay exponentially with delay. This delay profile can be characterized by just two parameters (both variable over the terrain), namely, the ratio (K0) of the average powers in the ?spike? and ?exponential? components and the decay time constant (τ0) of the ?exponential? component. No such simple structure appears to apply for delay profiles using omnidirectional antennas. For a directive antenna with a 32° beamwidth, we find that: (1) the statistical correlation between the profile parameters K0 and τ0 is negligible; (2) these parameters are relatively insensitive to antenna height and path length; and (3) over each measured region (Illinois and New Jersey), K0 and τ0 have median values close to 8 dB and just below 0.2 μs, respectively. Moreover, we have found simple probability distributions that accurately portray the variability of K0 and τ0 over the terrain